A DISCOURSE ON THE ORIGIN AND MIGRATION OF THE ABOHOF THE LOWER NIGER OF NIGERIA - Opone, Paul O. (International Review of Humanities Studies, 2021)
This study focuses on the origin and migration of the Aboh of the lower Niger. This is an area of African scholarship that has generated much controversy because it greatly determines group identities in their present locations. This is even more so with the Aboh whose history is characterized by multiple claims of origins which have so far denied them a pan identity. The aim of this study is, therefore, to address the contentious issues in their origin and migration, thereby opening up new vistas of historical scholarship. Sources collected for this study were both primary and secondary. The primary sources are made up of intelligence reports collected from the National Archives, and personal interviews with knowledgeable individuals on the subject. The secondary sources are library-based where relevant materials on the subject were consulted. The study deployed the historical method of analysis to address the subject. It argues that the dominant narrative of Aboh origin does not reflect the reality on ground, but constructed for political purposes. The conclusion suggests how best Aboh origin should be understood with the evidence provided by this study.